Biographical perspectives of educational transitions - Živoder, Andreja (Teorija in praksa, 2016)
The article examines the biographical perspective of educational transitions through the methodological approach of qualitative case studies. An in-depth analysis of individual cases provides important insights into the processes of educational decision-making and reveals the key challenges young people today face when planning their future educational pathways. The article identifies and interprets the main findings with regard to a wider societal and institutional framework, which structures and shapes the individual lives of students: unequal access to education, the structure of the education system, institutional support, the processes of individualisation, de-fragmentation of life courses, familialisation and parental involvement.
Keywords: Choice; Education; Izbira; izobraževalni prehodi; Izobraževanje; odločanje; Parents; School children; Slovenia; Slovenija; Starši; Učenci